PAISAGEM: CONCEPÇÕES, ASPECTOS MORFOLÓGICOS E SIGNIFICADOS / Landscape: conceptions, morphological aspects and meanings - Vicente de Paulo de Paulo da Silva (Sociedade & Natureza)
The aim of this study is to discuss about the concept of landscape under the morphologicalperspectives and its meanings. Therefore, firstly it is important to look for to understand theconcept as it is presented and, afterwards, analyze it from the point of view of several meaningsthat could be attributed to that category. The landscape presents several privileged dimensionsthrough several matrixes. Therewith it has a morphological dimension and a functional dimension,a spatial dimension and a historical dimension. (CORRÊA E ROSENDAHL, 1998). Accordingto these authors the morphological dimension is defined as a set of forms created bynature, as well as by human action, so that, when presenting relationships with several parts,it defines its functional dimension. That human action, along the time, will define the historicaldimension, while its occurrence in certain earth surface area gives it the spatial dimension. Atlast, as a carrier of meanings and expressing values, beliefs, myth and utopia, the landscapehas a symbolical dimension.